Etiology, Prevalence, and Risk Factors of Bacterial Meningitis in Children Under Five at Nakuru County Referral Hospital, Kenya - Emily CHEWOREI; Titus SUGE (African Journal of Pharmacy and Alternative Medicine, 2026)
Bacterial meningitis remains a significant public health burden among young children in resource-limited settings. This study aimed to determine the etiology, prevalence, and associated risk factors of bacterial meningitis in children under five admitted to Nakuru County Referral Hospital, Kenya. A retrospective analysis was conducted on medical records of 105 children diagnosed with bacterial meningitis between 2017 and 2021. Streptococcus pneumoniae was the most prevalent pathogen, accounting for 42.9% of cases, followed by Haemophilus influenzae (30.5%). The mean age of affected children was 2.03 years (SD = 0.833). Age, weight, and gender were significantly associated with the development of bacterial meningitis (p < 0.001). Children attending daycare had a significantly higher risk compared to those not attending daycare (OR =1.996, p = 0.0113). Vaccination status also emerged as a significant risk factor (OR = 1.519, p = 0.0417). These findings underscore the critical need for early diagnosis, appropriate antimicrobial therapy, and enhanced vaccination coverage to mitigate the burden of bacterial meningitis. Strengthening preventive measures and adherence to treatment guidelines are essential for improving child health outcomes in this region